2015
DOI: 10.1371/journal.pone.0124964
|View full text |Cite
|
Sign up to set email alerts
|

WDR5 Expression Is Prognostic of Breast Cancer Outcome

Abstract: WDR5 is a core component of the human mixed lineage leukemia-2 complex, which plays central roles in ER positive tumour cells and is a major driver of androgen-dependent prostate cancer cell proliferation. Given the similarities between breast and prostate cancers, we explore the potential prognostic value of WDR5 gene expression on breast cancer survival. Our findings reveal that WDR5 over-expression is associated with poor breast cancer clinical outcome in three gene expression data sets and BreastMark. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 45 publications
2
63
0
Order By: Relevance
“…Our findings are echoed by the report, which has revealed that WDR5 protein overexpression correlated with increased HDAC3 expression in 88 HNSCC samples as determined by immunohistochemistry . Thus, our findings together with previous reports provided experimental evidence that WDR5 is commonly overexpressed in human cancer including HNSCC . To initially identify the mechanisms for WDR5 expression, total frequency of genetic alternations of WDR5 in TCGA‐HNSCC samples was quite low, thus precluding genetic abnormalities as the primary mechanism for WDR5 overexpression.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Our findings are echoed by the report, which has revealed that WDR5 protein overexpression correlated with increased HDAC3 expression in 88 HNSCC samples as determined by immunohistochemistry . Thus, our findings together with previous reports provided experimental evidence that WDR5 is commonly overexpressed in human cancer including HNSCC . To initially identify the mechanisms for WDR5 expression, total frequency of genetic alternations of WDR5 in TCGA‐HNSCC samples was quite low, thus precluding genetic abnormalities as the primary mechanism for WDR5 overexpression.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have indicated that WDR5 is aberrantly overexpressed in several human cancers and associates with poor prognosis . Initially, to determine the expression of WDR5 in HNSCC, we utilized several publicly available databases including Oncomine, cBioPortal, and TCGA to interrogate the mutational landscape of WDR5 and its mRNA expression in HNSCC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, WDR5 has central roles in the proliferation of androgen-dependent prostate cancer cell, and its protein expression levels are positively correlated with poor survival in breast and bladder cancer. 15, 17, 18 Nevertheless, none of these studies has elucidated the functional mechanism of action of WDR5 in CRC metastasis. In our study, WDR5 upregulation was frequently observed in CRC cell lines and tissues, and its overexpression level could serve as an independent predictor for survival of CRC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The core subunit of the COMPASS-like complex WD repeatcontaining protein 5 (WDR5) recognizes the histone H3 amino-terminal tail, thus enabling its methylation on Lys4 (H3K4) (Ford & Dingwall, 2015). WDR5 has a pivotal role in tumor growth and proliferation (Carugo, Genovese et al, 2016, Chen, Xie et al, 2015, Mungamuri, Murk et al, 2013, differentiation (Ang, Tsai et al, 2011, Wang, Han et al, 2017 and metastasis (Lin, Wang et al, 2017, Malek, Gajula et al, 2017, Tan, Chen et al, 2017, showing deregulated expression in different cancers , Chen et al, 2015, Cui, Li et al, 2018, Dai, Guo et al, 2015, Ge, Song et al, 2016, Wu, Diao et al, 2018b. Moreover, mesenchymal genes are marked with H3K4me3 by WDR5 in breast cancer upon hypoxia treatment (Wu, Tsai et al, 2011), and in colorectal , prostate (Malek et al, 2017), and lung 26 tumor cells.…”
Section: Introductionmentioning
confidence: 99%